The “German-Turkish threat to India”, Iran’s occupation by Britain and British intervention in Transcaucasia and Transcaspia, 1914-1920 : Reply to critics from the Central Asian Research Centre and St. Antony’s College, Oxford University - Miroshnikov, L. I. [Lev Ivanovich]. (Moscow)
70 s.